An MVA-based vector expressing cell-free ISG15 increases IFN-I production and improves HIV-1-specific CD8 T cell immune responses - Falqui, Michela; Perdiguero, Beatriz; Coloma, Rocio; Albert, Manuel; Marcos-Villar, Laura; McGrail, Joseph Patrick; Sorzano, Carlos Óscar S.; Esteban, Mariano; Gómez, Carmen Elena; Guerra, Susana (Frontiers in Cellular and Infection Microbiology, 2023)
The human immunodeficiency virus (HIV), responsible of the Acquired Immune Deficiency Syndrome (AIDS), continues to be a major global public health issue with any cure or vaccine available. The Interferon-stimulated gene 15 (ISG15) encodes a ubiquitin-like protein that is induced by interferons and plays a critical role in the immune response. ISG15 is a modifier protein that covalently binds to its targets via a reversible bond, a process known as ISGylation, which is the best-characterized activity of this protein to date. However, ISG15 can also interact with intracellular proteins via non-covalent binding or act as a cytokine in the extracellular space after secretion. In previous studies we proved the adjuvant effect of ISG15 when delivered by a DNA-vector in heterologous prime-boost combination with a Modified Vaccinia virus Ankara (MVA)-based recombinant virus expressing HIV-1 antigens Env/Gag-Pol-Nef (MVA-B). Here we extended these results evaluating the adjuvant effect of ISG15 when expressed by an MVA vector. For this, we generated and characterized two novel MVA recombinants expressing different forms of ISG15, the wild-type ISG15GG (able to perform ISGylation) or the mutated ISG15AA (unable to perform ISGylation). In mice immunized with the heterologous DNA prime/MVA boost regimen, the expression of the mutant ISG15AA from MVA-Δ3-ISG15AA vector in combination with MVA-B induced an increase in the magnitude and quality of HIV-1-specific CD8 T cells as well as in the levels of IFN-I released, providing a better immunostimulatory activity than the wild-type ISG15GG. Our results confirm the importance of ISG15 as an immune adjuvant in the vaccine field and highlights its role as a potential relevant component in HIV-1 immunization protocols.